Hubungan Pengetahuan dan Sikap Terhadap Kecemasan Lansia Comorbid dengan Pemberian Vaksinasi Covid-19 - Ernawati Ernawati; Naziyah Naziyah; Andi Julia Rifiana (Universitas Malahayati Lampung, 2022)
ABSTRACT The problem that is currently happening in Indonesia is how to prevent COVID-19 infection through the COVID-19 vaccine. Several types of COVID-19 vaccines are currently being developed. The main thing to control the pandemic is how to increase immunity or herd immunity, one of which is by giving the COVID 19 vaccination with priority targets among the elderly (elderly) who are over 60 years of age. This research aimed to determine the relationship between knowledge and attitudes towards comorbid elderly with the provision of COVID-19 vaccination in Cikendung Pulosari Pemalang. This research was a descriptive cross-sectional study. The sample in this research was 208 people with a purposive sampling technique. The research instrument consisted of a knowledge questionnaire, an attitude questionnaire, and an anxiety questionnaire. The data were analyzed using Rank Spearman and Chi-Square correlation. It is known that the results of the study show that there is a significant relationship between knowledge and anxiety of the comorbid elderly with the provision of COVID-19 vaccination (p-value = 0.000). Attitudes with comorbid elderly anxiety with the provision of COVID-19 vaccination (p-value = 0.000). Knowledge and attitudes are related to the anxiety of comorbid elderly with the provision of COVID-19 vaccination, COVID-19 vaccination must be carried out so that the body's immune system increases and the risk of contracting the COVID-19 virus are lower and to break the chain of COVID-19 spread so that this pandemic end quickly. Keywords: Knowledge, attitude, comorbid elderly anxiety, giving COVID 19 vaccination. ABSTRAK Permasalahan yang terjadi di Indonesia saat ini adalah cara untuk pencegahan infeksi COVID-19 melalui vaksin COVID-19. Beberapa jenis vaksin COVID-19 saat ini sedang dikembangkan. Pengendalian pandemic utamanya bagaimana meningkatkan kekebalan imunitas atau herd immunity, salah satunya dengan pemberian vaksinasi COVID-19 dengan sasaran prioritas kalangan masyarakat lanjut usia (lansia) yang berusia lebih dari 60 tahu. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan dan sikap terhadap lansia comorbid dengan pemberian vaksinasi COVID-19 di Cikendung Pulosari Pemalang. Penelitian ini adalah deskriptif cross-sectional. Sampel dalam penelitian ini berjumlah 208 orang dengan teknik purposive sampling. Instrumen penelitian terdiri dari kuesioner pengetahuan, kuesioner sikap, dan kuesioner kecemasan. Data dianalisis dengan korelasi Rank Spearman dan Chi-Square. Diketahui bahwa dari hasil penelitian menunjukkan terdapat hubungan yang signifikan antara pengetahuan dengan kecemasan lansia comorbid dengan pemberian vaksinasi COVID-19 (p-value=0.000). Sikap dengan kecemasan lansia comorbid dengan pemberian vaksinasi COVID-19 (p-value=0.000). Pengetahuan dan sikap berhubungan dengan kecemasan lansia comorbid dengan pemberian vaksinasi COVID-19, vaksinasi COVID-19 harus dilakukan supaya imun tubuh meningkat dan resiko tertular virus COVID-19 lebih rendah dan untuk memutus mata rantai penyebaran COVID-19 sehingga pandemi ini cepat berakhir. Kata Kunci: Pengetahuan, sikap, kecemasan lansia comorbid, pemberian vaksinasi COVID-19